ICTV Virus Taxonomy Profile: Hadakaviridae 2023. (5th January 2023) - Sato, Yukiyo; Turina, Massimo; Chiba, Sotaro; Okada, Ryo; Bhatti, Muhammad F.; Kotta-Loizou, Ioly; Coutts, Robert H. A.; Kondo, Hideki; Sabanadzovic, Sead; Suzuki, Nobuhiro; ,
Abstract : The family Hadakaviridae, including the genus Hadakavirus, accommodates capsidless viruses with a 10- or 11-segmented positive-sense (+) RNA genome. Currently known hosts are ascomycetous filamentous fungi. Although phylogenetically related to polymycovirids with a segmented double-stranded RNA genome and certain encapsidated picorna-like viruses, hadakavirids are distinct in their lack of a capsid ('hadaka' means naked in Japanese) and their consequent inability to be pelleted by conventional ultracentrifugation; they show ribonuclease susceptibility in host tissue homogenates. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Hadakaviridae, which is available at ictv.global/report/hadakaviridae.